PREDICTION OF LOW BIRTH WEIGHT BASED ON MATERNAL THIRD TRIMESTER WEIGHT AMONG MOTHERS AT A MATERNAL CLINIC IN JAKARTA, INDONESIA - Kusharisupeni Djokosujono; Wahyu Kurnia Yusrin Putra; Diah Mulyawati Utari; Isna Aulia Fajarini (Universitas Airlangga, 2021)
The occurrence of low birth weight (LBW) can be reduced by optimizing gestational weight gain. However, the gestational weight cannot be monitored properly as there are a lot of mothers who receive Antenatal Care (ANC) less than four times as recommended by WHO. Therefore, this study aimed to determine whether early third trimester gestational weight could predict the incidence of LBW among newborns. A cross-sectional study was conducted using secondary data from Anny Rahardjo Maternity Clinic’s registry. A total of 278 eligible data of pregnant mothers who visited the clinic in 2017–2018 was chosen as study subjects. The mean for weight of birth was 3112.77 ± 384.40 g and early third trimester was 63.52 ± 11.07 kg. The prevalence of LBW was 3.2%. Early third trimester weight was found as the dominant factor of LBW after controlling the length of gestation. Early third trimester weight is signifi cantly correlated with LBW (p < 0.001). The optimum cutoff point was 59.8 kg with AUC = 0.68 (CI 95% = 0.52 – 0.83), sensitivity 67%, specifi city 63%, positive predictive value 5.66%, and negative predictive value 98.2%. The early third trimester weight is able to predict LBW with optimal cutoff value 59.8 kg.